Determinants of business cycles in small scale macroeconomic models: The German case - Alfred Maussner; Julius Spatz (Universität Augsburg, Institut für Volkswirtschaftslehre, 2001)
We identify measures of shocks to total factor productivity and preferences from two real business cycle models and subject them to Granger causality tests to see whether they can be considered exogenous to other plausible sources of the German business cycle in the mid nineteen seventies and nineteen eighties. We find no evidence to reject the exogeneity of our shock measures. This results contrasts with similar studies for other countries that question the exogeneity of either productivity or preference shocks.
urn:nbn:de:bvb:384-opus4-712493
Keywords: E32; O47; 330; Real Business Cycles; Solow Residual; Granger CausalityRe